2019
DOI: 10.31344/ijhhs.v0i0.161
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Practice: Awareness among Women in Muar District

Abstract: Introduction: Breast cancer is the most common cancer among women. The most recent estimate indicated that there are more than 1.6 million new cases of breast cancer worldwide yearly.Objectives: To assess the level of awareness on breast cancer screening practice among women in Muar.Methods: This is a quantitative cross-sectional survey done on 383 respondents in Muar where participants’ age ranged from 18-80 years. The study used a two-step sampling method namely cluster and simple random sampling. Descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Correspondingly higher skilled birth attendance in India was linked to husband antenatal attendance as Men's understanding of pregnancy-related care and a gender-positive attitude improve maternal health care use and women's decision-making about their health care, and male presence during antenatal care appointments significantly raises the likelihood that women would give birth in institutions (Chattopadhyay, 2012). In Malaysia, the majority (94%) of the male partners accompanied their spouses to receive antenatal care (Marzo et al, 2018). Similarly in rural Bangladesh, it was found that husbands' involvement is a key factor associated with women's utilization of skilled Maternal and Newborn Health (MNH) services during pregnancy, childbirth and postpartum.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Correspondingly higher skilled birth attendance in India was linked to husband antenatal attendance as Men's understanding of pregnancy-related care and a gender-positive attitude improve maternal health care use and women's decision-making about their health care, and male presence during antenatal care appointments significantly raises the likelihood that women would give birth in institutions (Chattopadhyay, 2012). In Malaysia, the majority (94%) of the male partners accompanied their spouses to receive antenatal care (Marzo et al, 2018). Similarly in rural Bangladesh, it was found that husbands' involvement is a key factor associated with women's utilization of skilled Maternal and Newborn Health (MNH) services during pregnancy, childbirth and postpartum.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The husband's role also positively affects the delivery process and choosing of skilled birth attendants (Lestari et al, 2019). The situation can include financial support, accompanying ANC visits, setting up a place for delivery, and making decisions (Marzo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%